2015
DOI: 10.3382/ps/pev028
|View full text |Cite
|
Sign up to set email alerts
|

Robustness to chronic heat stress in laying hens: a meta-analysis

Abstract: Chronic heat is a major stress factor in laying hens and many studies on the effect of heat stress have been published. It remains difficult, however, to draw general conclusions about the effect of chronic heat stress on performance and its relationship with genetic and environmental factors, as these studies have been done under varying experimental conditions and using various experimental designs. A meta-analysis enabled us to make a quantitative review of the results from 131 published papers. The relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…Moreover, the pair-feeding experimental schedule showed that 70% of the reduced body weight gain in continuously stressed birds was due to the reduction in feed intake and 30% due to temperature exposure per se. These numbers confirm the hypothesis raised by the meta-analysis carried out by Mignon-Grasteau et al (2015) that the reduction in feed intake is the main cause of the effect on the other performance traits in heat stressed laying hensis also true for broilers. On the other hand, cyclical heat stress only affected growth due to the reduction in feed intake.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the pair-feeding experimental schedule showed that 70% of the reduced body weight gain in continuously stressed birds was due to the reduction in feed intake and 30% due to temperature exposure per se. These numbers confirm the hypothesis raised by the meta-analysis carried out by Mignon-Grasteau et al (2015) that the reduction in feed intake is the main cause of the effect on the other performance traits in heat stressed laying hensis also true for broilers. On the other hand, cyclical heat stress only affected growth due to the reduction in feed intake.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, it was found that the ADG and the ratio of feed gain of the HS group were significantly reduced compared with the PF group, although both groups received the same feed intake, which is in line with the study of Yunianto et al 23 Similarly, compared with birds raised under a continuous heat environment, the PF group at the same level of feed intake gained more body weight. 24,25 These results indicate that heat stress could not only inhibit appetite but also could induce some subsequent stress to reduce growth and this subsequent stress may influence nutrients digestibility or absorption.…”
Section: Discussionmentioning
confidence: 92%
“…Heat stress is a nonspecific body response resulting from the pathological increase in core body temperature without an increase in the temperature set point [5]. In livestock, HS can lead to a decrease in fertility, as well as reduced milk and meat production resulting in great economic losses [6][7][8]. Management measures for preventing HS, such as improvement of housing conditions, application of different nutritional regimens, or breeding heat tolerant breeds rats were used in a HS timed selection experiment at 42 °C for 30 min (H30, n = 9), 60 min (H60, n = 9), or 120 min (H120, n = 18) (Step 2).…”
Section: Introductionmentioning
confidence: 99%